Cardiac safety of the adjuvant Trastuzumab in a Moroccan population: observational monocentric study of about 100 patients - Aitelhaj, Meryem (BioMed Central, 2013)
BACKGROUND: Trastuzumab is a humanized monoclonal antibody that binds to the extracellular domain of the human epidermal growth factor receptor 2 (HER 2) and inhibits carcinoma cellular proliferation. Its use as an adjuvant for a period of one year is currently an internationally recognised standard for the treatment of localized breast cancer. Its use is generally well tolerated, with the most salient side effect being a particular cardiotoxicity that is typically manifested by an asymptomatic decrease in the left ventricular ejection fraction (LVEF) requiring careful monitoring before and during treatment. To evaluate the cardiac safety of trastuzumab we conducted a retrospective observational study of patients with HER2-positive localized breast cancer treated with trastuzumab between May 2008 and May 2010 in Morocco. FINDINGS: The study comprised of 100 patients. The average in LVEF before the start of trastuzumab was 70%, and at the end of treatment 66%, a decrease in absolute terms of 4%; this difference was statistically significant. 38% of the patients exhibited cardiotoxicity. 97% of our patients have completed treatment, of whom 23% with a provisional arrest because of a regressive fall in LVEF. A final arrest has been made in 3% of cases due to a non regressive reduction in LVEF. A symptomatic heart failure was found in three patients. Analysis of risk factors toxicity found a baseline LVEF higher in the patients who met cardiotoxicity than the rest of our sample. CONCLUSIONS: The cardiac safety in our study seems comparable with the literature data but located in the upper range of levels of toxicity. Cardiotoxicity is the major complication of Trastuzumab, of which LV dysfunction is the most common. Most instances are transient, asymptomatic and reversible.